Comparative Stability Assessment of Dual Versus Single Reinforcement Configurations in Mechanically Stabilized Earth (MSE) Walls - Hartono, Edi; Diana, Willis; Afifah Anis Tsamara , Ghina (Bulletin of Civil Engineering, 2026)
Mechanically stabilized earth (MSE) walls are widely used in transportation infrastructure due to their cost efficiency, constructability, and adaptability. However, the performance implications of different reinforcement configurations under combined static and seismic loads remain insufficiently quantified. This study examines a 7.2 m MSE wall reinforced with either dual 30 kN strips or a single 50 kN strip, analyzing internal, external, and global stability using both manual calculations and Limit Equilibrium Method (LEM) with Geo5. Geotechnical properties, reinforcement reduction factors, traffic surcharges, and seismic coefficients were incorporated following national design standards. Manual methods applied Rankine and Coulomb formulations, while Geo5 captured soil–strip interface behavior. Results indicate that the dual 30 kN configuration achieved higher tensile and external stability factors, offering enhanced load distribution and redundancy, particularly advantageous under seismic or high-surcharge conditions. The single 50 kN configuration exhibited higher breakage resistance and construction simplicity, suitable for static or cost-driven scenarios. Manual and numerical results were closely matched, with differences typically below 10%, supporting the validity of LEM for design verification. These findings underscore the need to tailor reinforcement strategies to site-specific conditions and performance objectives. Future research should explore hybrid configurations and long-term monitoring to optimize cost-performance trade-offs in MSE wall design.